Red crust: evidence for an early Paleozoic oceanic anoxic event. Issue 7 (2nd October 2020) - Langsford, N.; Raimondo, T.; Jago, J.
Abstract: Lower Cambrian carbonates of the Flinders Ranges, South Australia, feature a distinctive and laterally continuous hematitic horizon known as the Red Crust. Previously interpreted as a subaerial unconformity and major sequence boundary, we present conclusive paleontological and petrographic evidence that all occurrences of hematite are in the form of ferrimicrobialites constituting a component of the carbonate sediment. Newly described fossil assemblages including Gravestockia calcareous sponges, archaeocyaths and associated stereoplasm also indicate that deposition occurred in a shallow-water marine environment. The Red Crust is interpreted to reflect a widespread and dramatic shift to anoxic reducing conditions driven by ferruginous marine waters during the early Paleozoic, marking the oldest recognised Paleozoic oceanic anoxic event (OAE) of this type, coeval with the Cambrian explosion of life.